Analisis Usability Testing pada User Interface dalam Game Idle Breeder - James James; Agung Riyadi (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2021)
In today's development, children are used to using smart phones or smartphones. Most of these smartphones run on the Android or IOS operating system. In smartphones there are applications that can be used for various purposes. One type of these applications is games. In this case, there are still many users who play the game having difficulty understanding the layout and menus that have been presented in a game, making it difficult for users to play it. In this study the author will discuss the user experience in the game "idle breeder" Idle Breeder is a top-down game with an idle genre with a relaxing feel. The formulation of this research is how to design a user interface in the idle breeder game and also how to do analysis in terms of user experience from users. User experience focuses on the comfort and convenience of users in using idle breeder games (usability)